The Captagon Trade In Syria In The Eyes Of UNTOC: A Case Study - Bian Abdulraheem Alaqab (Science and Education Journal (SICEDU), 2026)
This study unpacks the explosive rise of Syria’s Captagon empire, tracing its evolution from battlefield stimulant to cornerstone of UNOC believed is a multi-billion dollar transnational drug trade. Against the backdrop of civil war, authoritarian rule, and economic collapse, the Syrian state’s alleged complicity in industrial-scale narcotics production has transformed the country into a narco-state—one that undermines both domestic law and international conventions like the UNTOC. The analysis explores Syria’s fragmented legal framework, enforcement gaps, and the limited success of current prevention efforts, while proposing future paths for international accountability. It also examines Syria’s role in regional trafficking networks and market countries, centring its population—and those of its trading partners—as victims of addiction and systemic exploitation. By revealing the staggering scale and strategic complexity of one of the most alarming narco-trafficking cases in recent UN and media reports, the study offers urgent lessons for a global community confronting state-enabled crime.